The theory of developing students’ communicative competence based on the Pirls International Assessment Program - Ne'matova Flora Baxtiyor Qizi (Goodwood Publishing, 2025)
Purpose: This study aimed to construct a theoretical framework for developing students’ communicative competence by integrating the principles of the PIRLS International Assessment Program. The objective was to demonstrate how PIRLS approaches reading literacy can enhance students’ comprehension, interpretation, and communication skills in diverse educational contexts. Research Methodology: This study used a quantitative survey with 50 respondents representing various user groups of BPS services. Data were collected via Likert-scale questionnaires and analyzed using SPSS and Excel through validity tests, gap analysis, and Importance-Performance Analysis (IPA). Results: The findings indicate that Uzbekistan has strategically integrated the PIRLS into its educational reforms through the Presidential Decree No. 5712 and Resolution No. 997, which emphasize international benchmarking and the development of a national evaluation system. PIRLS not only serves as a diagnostic tool but also guides the improvement of teaching methods, curriculum design, and communicative skills. Its implementation promotes reading comprehension, analytical thinking, and effective communication among primary students, thereby aligning national education with global standards. Conclusions: PIRLS should be viewed not merely as an evaluation mechanism but as a strategic opportunity to modernize education, enhance communicative competence and foster globally competitive learning. Limitations: This study is conceptually based and lacks empirical validation, and its focus on Uzbekistan may limit its applicability to other contexts. Contribution: This study contributes theoretically by linking the PIRLS to communicative competence development and practically by offering insights into integrating global literacy assessments into national education systems.